Hordeum vulgare (Barley grass) Scavenge Free Radical and Inhibits Formation of Advanced Glycation End Products Formation. - Nematiasgarabad, Pershia; Anamalay, Kirtani; Xiu, Qing Chong; Hor, Kuan Chan; Okechukwu, Patrick Nwabueze (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Advanced glycation end products (AGEs) formation is due to glycation of lipids, proteins, and nucleic acids. AGEs play a vital role in Diabetes Mellitus (DM) and cardiovascular complications and is enhanced by oxidative stress. Hordeum vulgare (Barley Grass) is a cereal plant of grass family poaceae and has been reported to exhibit antidiabetic and antioxidant characteristics and prevention of cardiovascular disease. Current experiment focused on the evaluation of antioxidant and anti-advanced glycation end products formation effect of Hordeum vulgare water extract. Methods: Free radical scavenging ability of Hordeum vulgare water extract, was evaluated using DPPH, nitric oxide, hydrogen peroxide, lipid peroxidation, FRAP and metal ion chelating. Total phenolic content of Hordeum vulgare was also analysed. In-vitro antiglycation activity was done using BSA-MGO, BSA-Glu. Phytochemical screening was performed to detect the presence of flavonoids, saponins, tannins, steroids and terpenoids. Results: The results showed Hordeum vulgare water extract ameliorated the formation of AGE and scavenge free radical from DPPH, Nitric oxide, hydrogen peroxide, Lipid peroxidation, FRAP and Metal ion chelating. Phytochemicals such as saponins, tannins, flavonoids, steroids and terpenoids were detected in Hordeum vulgare water extract. Conclusion: Hordeum vulgare water extract reveals antiglycation and free scavenging properties.